Percutaneous balloon angioplasty in dialysis fistula stenosis - Szczerbiński, Jakub; Tarczyński, Maciej; Bojakowski , Krzysztof; Andziak, Piotr (Wiedza Medyczna, 2023)
The formation of stenosis in dialysis fistula disturbing blood flow is the most frequent complication and factor limiting its long-term function. Depending on the time and location stenosis lead to various clinical symptoms, triggering dialysis impairment. Due to its minimally invasive nature and high efficacy, percutaneous transluminal angioplasty is the treatment of choice for dialysis fistula stenosis in most locations. An important limitation of angioplasty is the significant risk of recurrent stenosis. Most procedures are performed by puncturing the fistula, performed either in line with the blood flow or opposite to the blood flow, depending on the location of the stenosis. Due to technical differences in dialysis fistula angioplasty – higher pressures of the insufflations used, shorter distance between the stenosis and the vascular access site – dedicated medical devices have been developed: balloon catheters on a shorter shaft, allowing higher insufflation pressures (up to 40 atmospheres). To reduce the risk of recurrent stenosis, drug coated/eluting balloons are also used during such surgeries.